ROLE OF KATI BASTI AND PATRA POTTALI SWEDA IN THE MANAGEMENT OF GRIDHRASI- A CASE STUDY (AYUSHDHARA, 2021)
The modern busy lifestyle of these days leads to several lifestyle disorders. Sciatica is one of the locomotory disorder occurs due to improper sitting posture, heavy weight lifting, stress injury and trauma to the spine. This disease became a great concern to the working people. Sciatica can be correlated with Gridhrasi in Ayurveda which is characterized as Ruk (pain), Stambha (stiffness), tingling sensation and numbness of lower limb. Gridhrasi is a type of Vatavyadhi mentioned in Ayurveda classics. Ayurveda through its advance treatment i.e. Panchakarma (Bio purification) eliminates the causative factors for disease. A male patient presented with signs and symptoms of Gridhrasi (sciatica) and MRI report suggesting of disc diffuse and disc protrusion and mild thecal compression. So In the present single case study patient was treated with Patra pottali sveda and Kati basti with some oral medicine. Both the therapies were effective in relieving symptoms like pain, stiffness, pricking sensation and numbness of leg.